Cultural Analysis of Female Cross-Gender Expression in Social Networks: A Case Study of Image Presentation in Douyin Short Videosv - Chen, Xiyuan (International Journal of Social Sciences and Public Administration, 2024)
With the continuous development of the internet and the growing awareness of women's social consciousness, the forms of self-expression by women on digital platforms have become increasingly diverse. Among these, female cross-gender performance has emerged as a key strategy of self-presentation in social networks. This paper analyzes two distinct expression strategies on the Douyin short video platform to explore and critically reflect on current female cross-gender expressions. The explicit expression strategy employs makeup, cross-dressing, and role-playing to simulate male personas, challenging traditional gender stereotypes. The implicit expression strategy, on the other hand, mocks male “ bad habits ” through the imitation of male behaviors and the use of symbolic metaphors, carrying a satirical undertone. However, these strategies have their limitations: male images are often idealized and trivialized, reinforcing gender norms; and constrained by patriarchal frameworks, they fail to genuinely subvert gender roles and the gender binary. As a result, while female cross-gender expression challenges gender stereotypes, it also faces risks of being disciplined and misinterpreted.